Comparison Study on Degradation of Plastic Hygiene Products by Using Pleurotus ostreatus - Nor Ain Najihah Zulkifle (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To investigate abiotic degradation of diapers and sanitary pad by natural weathering. To analyse the biotic degradation of diapers and sanitary pad by using Pleurotus ostreatus. To examine the combination biotic and abiotic degradation on the efficiency of diapers and sanitary pad degradation.